Meta-analyses of the effect of flossing on ankle range of motion and power jump performance - Pisz, A.; Kralova, K.; Blazek, D.; Golas, A.; Stastny, P. (Baltic Journal of Health and Physical Activity, 2020)
Decreased ankle range of motion (ROM) leads to many disorders, ranging in severity from gait abnormalities to knee and pelvis injuries. Therefore, maintaining full ankle ROM is very important, especially for athletes, for whom ankle ROM may affect their results during competitions. Medical flossing is a technique used by physiotherapists to improve ROM. The aim of this review was to investigate the effect of medical flossing on ankle ROM according to the results in previous studies.